Radiographic Assessment of the Depth of the Troclear Groove and Patellar Diameter in Dogs - Carneiro, Rafael Kretzer; de Souza, Mariana de Jesus; Bing, Rafaela Scheer; Alievi, Marcelo Meller; Feliciano, Marcus Antônio Rossi; Ferreira, Marcio Poletto (Acta Scientiae Veterinariae, 2020)
Background: Patellar luxation is an alteration of bone development for which the indicated treatment is surgery. Failure to correct it may result in clinical worsening. The most commonly used surgical approach is the transposition of the tibial crest with trochleoplasty, which aims to accommodate 50% of the patella in the trochlea. The femoral groove and trochlea can be evaluated radiographically by tangential projection, tomography, or ultrasonography; however, all these methodologies have limitations. The objective of this study was to evaluate the depth of the trochlear groove in three regions and to compare it with the patellar diameter on simple mediolateral radiographic images. Materials, Methods & Results: Fifty non-paired pelvic limbs of adult dogs of a specific breed, weighing less than 40 kg and without orthopedic changes, were used. In the mediolateral radiographic projection, three evaluators measured the femoral trochlear sulcus at three different points and the patellar diameter. After imaging examinations, all limbs were skeletonized, and the trochlea and patella were measured with a digital caliper in the same regions as that of the radiographic measurements. All post-skeletonization calculations were performed by an evaluator. The highest mean radiographic and ex vivo trochlear depth was 3.4 ± 1.2 mm and 2.7 ± 0.8 mm, respectively. The lowest mean radiographic and ex vivo patellar diameter was 7.7 ± 1.7 mm and 7.9 ± 1.6 mm, respectively. The average relationship between the trochlear depth and patellar diameter was less than 50% in all animals, with the highest radiographically determined ratio being 44.15% and that determined ex vivo as 34.17%. The mean patellar diameter calculated radiographically was similar among the animals. Discussion: Radiographic images made it possible to assess the patella and bone surface regions of the femoral condyles. A wide arthrotomy is necessary to perform sulcoplasty, and a simple preoperative planning examination, which can facilitate the measurement of the trochlear sulcus, is important to correctly determine the procedure. The fragments evaluated after skeletonization and radiographic evaluations showed an average relationship between the trochlear depth and patellar diameter of less than 50%, thus indicating that sulcoplasty may not be necessary in animals with a ratio less than 50%. The radiographic measurements in this study used specific reference points that became more difficult to reproduce after skeletonization reducing the reliability of ex vivo data. A large variation in results was noted in each area of the measured groove, thus indicating that the trochlear measurements should be breed-specific and that it is necessary to reduce the amplitude and standardize the values. The depths in the postskeletonization limbs resulted in lower means than that obtained radiographically. Notably, articular cartilage cannot be measured using radiology; thus, image-based measurements can overestimate the trochlear parameters. Developing histopathological evaluations, determining cartilage thickness by race, and evaluating the association with measurements using imaging techniques can enhance the accuracy of the results. The methodology for measuring the diameter of the patella was radiographically reliable; however, the mean value obtained cannot be extrapolated to all animals. We thus recommend that this evaluation be standardized based on race and on a case-by-case basis. Based on the results obtained, there is wide variation in the depth of the trochlear groove in dogs. Trochleoplasty is important; however, it is essential that the surgeon determines whether this surgical trauma is necessary.